Effect of cyclophosphamide on the growth of Rickettsia sennetsu in experimentally infected mice. - Tachibana, N (1975)
The growth rate of Rickettsia sennetsu, the etiological agent of sennetsu rickettsiosis, a special type of infectious mononucleosis found in western Japan, is very low when the ordinary experimental methods used for other members of the rickettsiae are employed. Attempts have been made to increase its growth the rickettsiae are employed. Attempts have been made to increase its growth rate in cells and animals. By treating mice with cyclophosphamide, considerable enhancement of growth of the rickettsia was observed. In the drug-treated mice, infective titers expressed as mean lethal dose in the spleens reached 10(8,5) in animals treated by the intraperitoneal route three times at 5-day intervals with 0.33 mg/g (body weight). Infective titers in drug-treated mice were more than 100-fold above those of the infected non-drug-treated mice. In peritoneal cells of drug-treated mice rickettsial particles were observed in great abundance. The numbers of cells containing rickettsiae almost paralleled the infective titers of the spleens in each group in mice. Lymph nodes and spleens of the drug-treated mice diminished in size during infection.